logo for solving-math-problems.com
leftimage for solving-math-problems.com

Solve the Equation










































Use logarithms to solve the following equation for x

Convert each side of the equation to a log with the same base.

Set the terms within the log functions on each side of the equation equal to one another, and then solve for x

7.3^(2x + 1) - 4 = 6

Comments for Solve the Equation

Click here to add your own comments

Apr 17, 2012
Solve the Equation
by: Staff


Question:

7. 3^(2x+1)-4=6



Answer:


3^(2x+1) - 4 = 6

3^(2x+1) - 4 + 4 = 6 + 4

3^(2x+1) + 0 = 6 + 4

3^(2x+1) = 6 + 4

3^(2x+1) = 10



Log₃[3^(2x+1)] = Log₃(10)

2x+1 = Log₃(10)

2x + 1 - 1 = Log₃(10) - 1

2x + 0 = Log₃(10) – 1

2x = Log₃(10) - 1

2x/2 = [Log₃(10) - 1]/2

x*(2/2) = [Log₃(10) - 1]/2

x*(1) = [Log₃(10) - 1]/2

x = [Log₃(10) - 1]/2

x ≈ 0.5479516371447






Thanks for writing.

Staff
www.solving-math-problems.com



Nov 19, 2013
equation
by: Anonymous

find b if p=105 and r = 77 7/9%

Click here to add your own comments

Join in and write your own page! It's easy to do. How? Simply click here to return to Math Questions & Comments - 01.



Copyright © 2008-2015. All rights reserved. Solving-Math-Problems.com